Musics of the Free State: Reflections on a Musical Past, Present, and Future. Martina Viljoen, ed. 2015. Zagreb: Croatian Musicological Society. 7 colour photographs, 2 maps, 9 tables, 28 music examples, index, 362pp. - Heunis, Daniela (International Library of African Music, 2016)
pages: 224-226
Keywords: African Music